Evaluation of the correlation between pre-anaesthetic P-POSSUM score, ultrasound muscle assessment and frailty index on perioperative outcome – An observational trial - Sanchi Sunil Bhalerao; Vanita Ahuja; Deepak Thapa; Sukanya Mitra; Ashok K. Attri; Sudesh K. Arya; Sidharth Garg (Indian Journal of Anaesthesia)
Background and Aims: Bedside muscle ultrasonography has emerged as a clinical tool for sarcopenia and perioperative outcomes. We aimed to find a correlation between the pre-anaesthetic Portsmouth Physiological and Operative Severity score for the enumeration of mortality and morbidity (P-POSSUM), Fried Frailty Phenotype (FrFP) and ultrasound-guided (USG) muscle cross-sectional area (CSA) with morbidity and mortality outcomes in elective surgeries . Methods: This prospective observational trial included 150 patients aged 18–80 years undergoing low-risk (n = 50), intermediate-risk (n = 50), and high-risk (n = 50) surgeries. Preoperative P-POSSUM scores, USG CSA of psoas major and rectus femoris muscles and FrFP were recorded. Postoperative outcomes on days 1, 2 and 3 and then until patient discharge were observed. A P value < 0.05 was considered statistically significant. Results: Demographics of patients were similar in age, gender, weight, body mass index and pre-frail status. A strong correlation coefficient was observed for physiological score, operative severity score, CSA of psoas major and CSA of rectus femoris. A weak strength correlation coefficient was observed between FrFP and CSA of psoas major, regarding 30-day morbidity and mortality. The area under the curve (AUC) - 0.74 for psoas major had moderate predictive ability, and AUC-0.84 for rectus femoris showed a strong predictive ability against 30-day mortality in high-risk surgeries. The Hosmer–Lemeshow goodness-of-fit test analysis revealed a mortality ratio of 0.98. Conclusion: P-POSSUM and CSA of psoas major and rectus femoris had a statistically significant positive correlation to predict perioperative 30-day mortality in survivor versus non-survivor patients of high-risk surgeries.